O manejo clínico da transferência em grupos de crianças com dificuldades graves no desenvolvimento emocional. - Galvão, Vinícius Gomes (2008)
The present research is a study in theory of the clinic, inspired by the practical one of the psychoanalysis with children carried through by the author, enters the years of 2004 and 2006, in the Centro de Pesquisa em Psicanálise e Linguagem (CPPL), and through a dialogue between this practical and the psychoanalytical theory, aim at to reflect on the handling of the transference in groups of children with serious difficulties in the emotional development. By means of the presentation of the work carried through for the CPPL, as well as of a deepening in the ideas of Winnicott on the o emotional development and the transference, it searchs to analyze the importance of the use of the contratransference and the subjetal transference in the work with the related children.